Decoding Sustainable Lifestyles: A Comprehensive Analysis of Life-‎Style Factors and Their Impact on Environmental Sustainability ‎Ratings - Guven, Ejder; Balcioglu, Yavuz Selim; Demirci, Fatma Gulcin; Bilgen , Ayşe; Karakaya , Turhan (International Journal of Accounting and Economics Studies, 2025)
As global environmental crises escalate, understanding how individual lifestyle factors affect sustainability outcomes is essential for informing effective interventions with measurable economic and environmental benefits. A cross-sectional survey was conducted with 499 participants across urban, suburban, and rural areas. Participants completed measures for 19 variables categorized under six domains: ‎demographics, diet and consumption, transportation and energy use, environmental behaviors, resource usage, and social/physical activities. ‎Transportation mode emerged as the strongest predictor of sustainability. Participants who primarily walked scored significantly higher, with ‎‎84.6% classified as high sustainability performers, compared to only 20% of car users. Diet type also significantly influenced ratings: plant-based diet adherents scored 4.37 on average, with 80.2% rated highly sustainable, versus 2.26 and 28.5% for those consuming animal-based diets. Environmental awareness exhibited a threshold effect; participants with awareness levels 4-5 showed 88% high sustainability, ‎whereas those at levels 1-3 averaged 28%. Six key behaviors, never using plastic, walking, a plant-based diet, limited clothing purchases, ‎renewable energy use, and composting, were associated with average sustainability ratings above 4.3. High-sustainability individuals used ‎‎39.2% less electricity and 36.0% less water than their lower-rated counterparts, representing substantial resource cost savings. Suburban ‎residents demonstrated the highest sustainability rates (67.9%), surpassing urban (47.4%) and rural (46.4%) populations. These findings ‎identify priority areas for promoting sustainable lifestyles and highlight the economic benefits of targeted behavioral interventions through ‎reduced resource consumption and associated cost savings‎.